The origin of Wxla provides new insights into the improvement of grain quality in rice. Issue 5 (26th March 2021) - Zhou, Hao; Xia, Duo; Zhao, Da; Li, Yanhua; Li, Pingbo; Wu, Bian; Gao, Guanjun; Zhang, Qinglu; Wang, Gongwei; Xiao, Jinghua; Li, Xianghua; Yu, Sibin; et al.
Abstract: Appearance and taste are important factors in rice ( Oryza sativa ) grain quality. Here, we investigated the taste scores and related eating‐quality traits of 533 diverse cultivars to assess the relationships between—and genetic basis of—rice taste and eating‐quality. A genome‐wide association study highlighted the Wx gene as the major factor underlying variation in taste and eating quality. Notably, a novel waxy ( Wx ) allele, Wx la, which combined two mutations from Wx b and Wx in, exhibited a unique phenotype. Reduced GBSSI activity conferred Wx la rice with both a transparent appearance and good eating quality. Haplotype analysis revealed that Wx la was derived from intragenic recombination. In fact, the recombination rate at the Wx locus was estimated to be 3.34 kb/cM, which was about 75‐fold higher than the genome‐wide mean, indicating that intragenic recombination is a major force driving diversity at the Wx locus. Based on our results, we propose a new network for Wx evolution, noting that new Wx alleles could easily be generated by crossing genotypes with different Wx alleles. This study thus provides insights into the evolution of the Wx locus and facilitates molecular breeding for quality in rice. Abstract : Wx la is derived from intragenic recombination of the Wx b and Wx in alleles, and Wx la rice grains have a transparent appearance and excellent eating quality. The study of Wx la provides insight on the evolution of the Wx gene and suggests avenues for improvement of rice grain quality.